Micobacteriosis en peces ornamentales y su posible implicación en la salud pública. Revisión (2021)
There are different difficulties related to health in the aquaculture industry for ornamental fish, especially infectious diseases of bacterial origin, which cause a high mortality rate that could become an environmental emergency, in the worst case. One of the common bacterial diseases, reported in ornamental fish, is mycobacteriosis. Some factors associated with the above are the poor physical and chemical conditions of the water in which these animals are sustained, as well as the management of the production system in general, therefore some of these problems could have direct implications for public health.